Harmonic feature of 27.5 kV traction power system in a Chinese high‐speed railway - Yadong Fan; Ding Hu; Wen Chen; Liming Gao; Jianping Wang; Mi Zhou; Jianguo Wang; Chang He (IET Electrical Systems in Transportation)
Abstract The key to controlling harmonics in high‐speed railways is to get information on its harmonic feature. In this study, a continuous 24 h harmonic observation is carried out in Ji'an West traction substation of a typical Chinese high‐speed railway. In both the 24 h operating period and the two train driving processes, the features of harmonics of 27.5 kV buses are studied under multiple operating modes, which finds that the voltage and the current harmonic content mainly consist of low‐order harmonics below the 11th order with high‐order harmonics that ranges from 13th to 31st and 89th to 99th order. The law that the harmonic distribution changes with the load current is derived. Calculation results show a power function relationship between total harmonic distortion and bus current. In regenerative braking modes, the harmonic content is higher than traction with less high‐order harmonics. Finally, the authors find an admittance matrix coupling between the 3rd to the 31st order harmonic voltage and current for simplified modelling of the harmonic transmission.